Bahasa Inggris - Ika Uswatun Hasanah; Maria Ulfa; Sri Yamtinah; Mohammad Masykuri; Bakti Mulyani; Ari Syahidul Shidiq (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this experiment was to determine whether or not there were differences in the learning model between Process-Oriented Guided Inquiry Learning (POGIL), Problem Based Learning (PBL), and Teacher-Centered Learning (TCL) with the application of HOTS questions in their learning on students' critical thinking skills. This study used a quasi-experimental research design with the static group pretest-posttest design. The sampling technique used the cluster random sampling technique. The population of this research is the students of class XI MIPA SMA Negeri Gondangrejo in the academic year 2021/2022. The results showed that there were differences in students' critical thinking skills in the POGIL and PBL learning models with conventional learning, all three of which used the application of HOTS questions in their learning. This is based on the significant value of the One-Way ANOVA test, a significance value of <0.05 is obtained, which is 0.000, which means that H0 was rejected. Then, based on the calculation of the N-gain score for each POGIL, PBL, and TCL learning model, the results obtained are 0.71 in the high category; 0.54 in the medium category; and 0.39 in the medium category. However, based on the results of the Post Hoc-Scheefe test between the POGIL and PBL learning models, a significance value of > 0.05 was obtained, which was 0.098, so it could be concluded that there was no significant difference between the POGIL and PBL learning models on critical thinking skills. Therefore, both POGIL and PBL learning models can help improve students' critical thinking skills. The average critical thinking ability in the POGIL experimental class, PBL experimental class, and control class after treatment was 69.44%, 68.54%, and 59.72%.